A Case of Facial Papular Elastorrhexis - Yang X; Lei X; Zhang J; Chen Z (Dove Medical Press, 2022)
Xiaojing Yang,1 Xuan Lei,2 Jianzhong Zhang,1 Zhou Chen1 1Department of Dermatology, Peking University People's Hospital, Beijing, People's Republic of China; 2Department of Emergency, Beijing Chest Hospital Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Zhou Chen, Department of Dermatology, Peking University People's Hospital, # 11. Xizhimen South St, Beijing, 100044, People's Republic of China, Tel +86-10-88325472, Fax +86-10-88325474, Email chenzhou54@sohu.comAbstract: Papular elastorrhexis (PE) is a rare disorder of dermal elastic fibers, which presents as firm, hypopigmented papules, commonly distributed on the trunk and extremities. The facial area is rarely involved. We report the case of a 47-year-old woman with multiple asymptomatic, soft, skin-colored facial papules whose histopathological features are compatible with PE. Facial PE may be a variant of PE, and special staining in showing changes in both elastic and collagen fibers may be of great value in diagnosis.Keywords: papular elastorrhexis, facial area, elastic fibers, collagen fibers, case report